Association of Admission HbA1c Levels and Clinical Outcomes in Patients with Large Vessel Occlusion Following Endovascular Treatment: A Secondary Analysis of RESCUE BT Trial - Gao F; Tan X; Li L; Zhou C; Guo C; Yang J; Liu G; Wang L; Shi X; Yang S; Ma J; Xu X; et al. (Clinical Interventions in Aging, 2025)
Fei Gao,1,* Xiaolin Tan,2,* Linyu Li,1,3,* Chao Zhou,4 Changwei Guo,1 Jie Yang,1 Guojian Liu,1 Lilan Wang,1 Xiaolei Shi,1 Shihai Yang,1 Jinfu Ma,1 Xu Xu,1 Dahong Yang,1 Wenzhe Sun,1 Nizhen Yu,1 Shitao Fan,1 Rui Xu,1 Jiaxing Song,3 Wenjie Zi,1 Zhenying Shang5 1Department of Neurology, Xinqiao Hospital and The Second Affiliated Hospital, Army Medical University (Third Military Medical University), Chongqing, People’s Republic of China; 2Department of Neurology, Meishan Second People’s Hospital, Sichuan, People’s Republic of China; 3Department of Neurology, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 4Department of Neurology, Drum Tower Hospital, Medical School and The State Key Laboratory of Pharmaceutical Biotechnology, Nanjing University, Jiangsu, People’s Republic of China; 5Department of Neurology, The Affiliated Hospital of Xuzhou Medical University, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenjie Zi, Department of Neurology, Xinqiao Hospital and The Second Affiliated Hospital, Army Medical University (Third Military Medical University), No. 183 Xinqiao Main Street, Shapingba District, Chongqing, 400037, People’s Republic of China, Email ziwenjie1981@163.com Zhenying Shang, Department of Neurology, The Affiliated Hospital of Xuzhou Medical University, Jiangsu, 221002, People’s Republic of China, Email drshang01@163.comBackground: This study aimed to analyze the association of HbA1c levels and outcomes in patients with large vessel occlusion (LVO) undergoing endovascular treatment (EVT).Methods: Patients with recorded HbA1c values were enrolled from The Endovascular Treatment With vs Without Tirofiban for Patients with Large Vessel Occlusion Stroke (RESCUE BT) trial. We defined the high HbA1c levels as a plasma level of HbA1c > 6.5%. The primary outcome was good outcome (defined as a modified Rankin Scale score (mRS) of 0– 2) at 90 days, secondary outcomes included other clinical outcomes (excellent outcome, mRS 0– 1) at 90 days, mortality at 90 days, symptomatic intracerebral hemorrhage (sICH) within 48h, and any intracerebral hemorrhage (ICH).Results: Among the 560 patients with HbA1c values, 133 (23.7%) patients were in the HbA1c > 6.5% group, and 427 (76.3%) patients were in the HbA1c ≤ 6.5% group. In multivariable analysis, the HbA1c > 6.5% group showed a significant negative association with good outcomes at 90 days (mRS 0– 2; adjusted odds ratio [aOR], 0.57; 95% CI 0.37– 0.88; P = 0.01), and the HbA1c > 6.5% group was significantly associated with increased mortality (aOR, 2.06; 95% CI 1.20– 3.54; P = 0.009). There were no significant differences in the incidence of sICH between the two groups. Additionally, the subgroup analysis showed an interaction effect between high HbA1c levels and age.Conclusion: Our results demonstrated that elevated HbA1c levels were associated with poor clinical outcomes in LVO patients who underwent EVT.Keywords: HbA1c levels, acute ischemic stroke, large vessel occlusion, endovascular treatment, RESCUE BT trial